2010
DOI: 10.1063/1.3271252
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in ion beam current with layered-glows in a constricted dc plasma ion source

Abstract: High current mode has been discovered and investigated in a constricted dc plasma ion source. As discharge currents exceed a certain threshold, voltage to sustain the constricted dc plasma suddenly falls down to almost half of the value. In this sense, constricted dc plasmas can be sustained at much higher current than in conventional mode operation at a fixed discharge voltage. Phenomenally, several discrete layered-glows are created between an anode glow and a cathode glow. The layers are thin and divided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Applied voltages were maintained as almost constant, even when discharge currents increased up to 150 mA, showing fully developed state plasmas between the electrodes. This may be explained by a "layered-glows mode" which plays a crucial role on the relation of higher discharge currents with applied voltages only at a hollow-anode plasma source [9]. Hence, we intensively focused on plasma jets, generated by the high current mode, after voltage transition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applied voltages were maintained as almost constant, even when discharge currents increased up to 150 mA, showing fully developed state plasmas between the electrodes. This may be explained by a "layered-glows mode" which plays a crucial role on the relation of higher discharge currents with applied voltages only at a hollow-anode plasma source [9]. Hence, we intensively focused on plasma jets, generated by the high current mode, after voltage transition.…”
Section: Resultsmentioning
confidence: 99%
“…This is explained by the formation of stable plasma jets with a high discharge current after the voltage transition, in the section of VI characteristics. Additionally, the report [9] of experimental analyses on the plasma phenomena inside the hollow-anode discharge source to maintain the discharge at a higher sustaining current, with high efficiency in constricted DC plasmas, is a clearer rationale for improving the efficiency of sputtering processes by the developed plasma source. future works, we will conduct sputtering processes using the developed plasma source and investigate its treatment on various substrates for verification of experimental conditions once more.…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…4 It was found that the conventional DC plasma was transited to layered-glow mode, forming a striation-like plasma, with high discharge current operation. Also, operation with hydrogen gas in the layered-glow mode showed 100 times higher ion beam current compared to the operation in conventional mode.…”
Section: Introductionmentioning
confidence: 98%
“…Constricted dc plasma ion source (or hollow anode discharge) is one example of utilizing small and dense discharges near extraction aperture. [4][5][6][7][8] A bright and small plasma ball which is attached to anode with smaller area compared to cathode is a key to make high current ion beam with high power efficiency. However, high operating pressures of 0.3-1 Torr and relatively high discharge voltages of 0.4-1 kV need to be overcome for better performance of ion source.…”
Section: Introductionmentioning
confidence: 99%